Indicadores de sustentabilidade para o turismo: uma análise no Parque Estadual Marinho de Areia Vermelha- PEMAV – PB - Silva, Thiago Araújo da (2019)
In compliance with the challenges agreed at the United Nations Conference on Environment and Development - UNCED in 1992 in Rio de Janeiro, the Global Agenda 21 has been a landmark in the discussions surrounding sustainability indicators. In this process of reorganization of systems, entities, companies, and governments, the sustainable ideal forces a new design of the tourism activity that has moved people and money, inserting itself naturally in the perspective of an administration within the social improvement, of the priority environmental, economic viability and institutional legitimacy '. The present research aims at proposing a set of sustainability indicators capable of portraying the current panorama of tourism activity in the Areia Vermelha Marine State Park-PEMAV, a conservation unit located in the municipality of Cabedelo, state of Paraíba. From the application of a more technical approach among the main studies in the area, the theoretical review on indicators of sustainability, tourism and conservation units, the research proposes a set of indicators, in four central dimensions, in an attempt to contribute to the scenario of environmental public policies. The work is characterized as a descriptive method, as a case study type and with a quantitative and qualitative approach, since it proposes indicators in a binary form, or proposes indicators of qualitative analysis. The field visits provided the knowledge of the area and the review of other studies allowed the choice of the best parameters to compose the proposed system. The results pointed out that, although massively technical, the work proved to be relevant by providing a system of indicators with advantages of adaptability, cohesive in its essence and with the possibility of measuring the reality of the studied object.